2020
DOI: 10.1016/j.patcog.2019.107129
|View full text |Cite
|
Sign up to set email alerts
|

A paired sparse representation model for robust face recognition from a single sample

Abstract: Sparse representation-based classification (SRC) has been shown to achieve a high level of accuracy in face recognition (FR). However, matching faces captured in unconstrained video against a gallery with a single reference facial still per individual typically yields low accuracy. For improved robustness to intra-class variations, SRC techniques for FR have recently been extended to incorporate variational information from an external generic set into an auxiliary dictionary. Despite their success in handling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…1). Here, we design a different function to simultaneously apply smoothness and non-negativity, utilisable in (2).…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Here, we design a different function to simultaneously apply smoothness and non-negativity, utilisable in (2).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Sparse representation problem is one of the most attractive and demanding topics in signal processing, image processing, computer vision and pattern classification research [1,2,3]. It is now explicitly observed that one can represent variety of signals/images/patterns with only few non-zero samples using an overcomplete matrix, the so-called dictionary.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sparse representation has received considerable interest from experts and researchers in many fields, which approximately reconstructs the query sample with a combination of training samples from all classes [41]- [44]. So far, SR has been extensively employed in many theoretical researches and industrial applications, especially in the fields of signal processing [45], [46] and pattern recognition [47], [48]. The mathematical expression of SR is compact.…”
Section: A Sparse Representationmentioning
confidence: 99%
“…In many practical face recognition systems, for example, law enforcement, entrance monitoring, intelligent video surveillance, criminal identification, the gallery set is typically designed using only one single sample per person (SSPP) [7] because of the limited storage and privacy policy. What makes the situation even worse is that the probe samples are usually captured with video surveillance cameras under unconstrained conditions [8,9]. Therefore, SSPP face recognition in this unconstrained environment is very challenging task due to, first, the strong intraclass variations such as illumination [10][11][12], pose [12,13], facial expression [14][15][16] and occlusion [17,18], and second, the lack of gallery samples.…”
Section: Introductionmentioning
confidence: 99%